Análise do desperdício dos cardápios servidos aos usuários antes e após mudança no sistema de distribuição de um restaurante universitário - MELO, Nathália de Oliveira (2023)
Introduction: In the administration of Food and Nutrition Units, waste is a major factor, since it is characterized by food leftovers. Evaluation of the rest-intake index assists in the understanding and analysis of waste. Ascertaining the factors that can intervene in waste, for the purpose of correcting, is advantageous for UAN. Objective: to verify the occurrence of wastage by analyzing the indices of rest intake and satisfaction in the period before and after the change in the distribution system of a university restaurant in the city of Belém-PA. Methodology: A descriptive, exploratory, quantitative and longitudinal study conducted in a university restaurant (RU) located in the city of Belém-PA, which serves 7 thousand meals a day between lunch and dinner, with service hours from 11:00 am to 2:00 p.m. 00 hours and from 17:45 to 19:15 hours the university community. For the research, the restingestion and the satisfaction of the users regarding the meals served by the UK during 30 days of the period from 2017 to 2019 were analyzed, in order to evaluate if the change in the distribution system of the RU generated some type of impact reduction of waste and increased satisfaction. Data were tabulated in the Microsoft Excel® 2016 program. Statistical analysis was performed on Bioestat 5.3 software. To verify the degree of dependence between categorical variables, the G test was applied, considering a level of significance (p-value 0,05). Results: It was verified through the analysis of the indices of rest ingestion and satisfaction of the users that the majority of the menus evaluated is within the range recommended by the literature, below 10% for the rest intake and with satisfaction classified as good and great by the user. However, a minimal reduction of the waste was observed with the change in the distribution system, which generated a small improvement in the results of the other ingestion performed. Conclusion: It was verified that the adoption of control measures in the production process, including the change in the distribution system, continues to be effective in reducing waste and user satisfaction.